Yield Performance of Some Promising Cocoa Clones (Theobroma cacao L.) at Dry Climate Condition - Agung Wahyu Susilo; Bayu Setyawan; Indah Anita Sari (Indonesian Coffee and Cocoa Research Institute, 2020)
El Nino effect as impact from global climate change needed anticipation effectively to keep cocoa production still give farmer benefit because effect of long dry season make some trouble in cocoa production. Cocoa production technology package that suitable in dry land needed for sustainable and empowerment cocoa production in marginal dry land. Principal component of this technology package is superior planting material because success of cocoa production depend on accuracy of selecting planting material. Indonesian Coffee and Cocoa Research Institute consistently carries out cocoa breeding programs aimed at overcoming problems in the field, specifically to obtain superior planting material that is tolerant to biotic and abiotic stress. This research method was carried out by observing 22 promising clones of cocoa that were planted in the Kaliwining experimental station in the 2013-2017 observation period, each clone planted in three blocks. The observed variables included estimation of production, resistance to VSD, helopeltis, and pod rot. Based on multivariate analysis, it was found that ICCRI 09 had a stable production performance from 2013 - 2017 while the promising clone of KW 641 had a special adaptation to dry conditions. Both of these clones have the potential to be developed as drought tolerant planting material to overcome the impact of climate change on cocoa production. The observation results of pest and disease attacks obtained a pattern that the clones that have tolerance to drought have good resistance to VSD.